Sub‐Picosecond Singlet Exciton Fission in Cyano‐Substituted Diaryltetracenes1. Issue 30 (10th June 2015) - Margulies, Eric A.; Wu, Yi‐Lin; Gawel, Przemyslaw; Miller, Stephen A.; Shoer, Leah E.; Schaller, Richard D.; Diederich, François; Wasielewski, Michael R.
Abstract Thin films of 5, 11‐dicyano‐6, 12‐diphenyltetracene (TcCN) have been studied for their ability to undergo singlet exciton fission (SF). Functionalization of tetracene with cyano substituents yields a more stable chromophore with favorable energetics for exoergic SF (2E(T1)−E(S1)=−0.17 eV), where S1 and T1 are singlet and triplet excitons, respectively. As a result of tuning the triplet‐state energy, SF is faster in TcCN relative to the corresponding endoergic process in tetracene. SF proceeds with two time constants in the film samples (τ=0.8±0.2 ps and τ=23±3 ps), which is attributed to structural disorder within the film giving rise to one population with a favorable interchromophore geometry, which undergoes rapid SF, and a second population in which the initially formed singlet exciton must diffuse to a site at which this favorable geometry exists. A triplet yield analysis using transient absorption spectra indicates the formation of 1.6±0.3 triplets per initial excited state.